CONJOINED TWIN FOETUS IN A SURTI BUFFALO- A CASE REPORT - Deshmukh, SG; Mehesere, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Conjoined twins are the most common cause of dystocia in cattle and buffalo. Conjoined twins develop when incomplete separation occurs after the development of the embryonic plate at 8 days. Depending upon the site of fusion the types of the twins may differ. Varying degrees of fusion occur but anterior duplication is more often seen in ruminants and swine (Arthur, 1956). Monsters consisting of two fetuses or more joined together are common in cow and buffalo (Sane et al., 1971), Solanki et al. (2011) and Sathiamoorthy et al. (2011) also reported similar case in cross bred cow. Structural or numerical duplication during the embryonic stage give rise to fetuses whose body structures are partially but not completely duplicated (Roberts, 1971). Conjoined twins arise from a single ovum and are monozygotic. Hancock (1954) and Arthur (1956) reported its occurrence to be about one in 1,00,000 bovines’ births.